Salvianolic Acid B Alleviates High Glucose-Induced Vascular Smooth Muscle Cell Inflammation by Upregulating the miR-486a-5p Expression - Man-Li Zhang; Man-Na Zhang; Hui Chen; Xia Wang; Kun Zhao; Xuan Li; Xuan Song; Fei Tong (Mediators of Inflammation)
The macrovascular complications of diabetes cause high mortality and disability in patients with type 2 diabetes mellitus (T2DM). The inflammatory response of vascular smooth muscle cell (VSMC) runs through its pathophysiological process. Salvianolic acid B (Sal B) exhibits beneficial effects on the cardiovascular system. However, its role and mechanism in diabetic vascular inflammatory response remain unclear. In this study, we found that Sal B reduced vascular inflammation in diabetic mice and high glucose- (HG-) induced VSMC inflammation. Subsequently, we found that Sal B reduced HG-induced VSMC inflammation by downregulating FOXO1. Furthermore, miR-486a-5p expression was obviously reduced in HG-treated VSMC. Sal B attenuated HG-induced VSMC inflammation by upregulating miR-486a-5p. Loss- and gain-of-function experiments had proven that the transfection of the miR-486a-5p mimic inhibited HG-induced VSMC inflammation whereas that of the miR-486a-5p inhibitor promoted HG-induced VSMC inflammation, thereby leading to the amelioration of vascular inflammation in the diabetic mice. Furthermore, studies had shown that miR-486a-5p inhibited FOXO1 expression by directly targeting its 3′-UTR. In conclusion, Sal B alleviates the inflammatory response of VSMC by upregulating miR-486a-5p and aggravating its inhibition of FOXO1 expression. Sal B exerts a significant anti-inflammatory effect in HG-induced VSMC inflammation by modulating the miR-486a-5p/FOXO1 axis.